Analisis Kesalahan Penyelesaian Soal Cerita pada Materi Persamaan Linier Satu Variabel terhadap Efikasi Diri Siswa - Muhammad Yamin; Amrullah; Tabita Wahyu Triutami; Sri Subarinah (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
Errors that are often made by students in solving math problems in the form of stories are such as errors in understanding concepts, errors in changing story problems in mathematical form and operating errors. Lack of self-confidence of students is one of the contributing factors. This study aims to describe the level of self-efficacy and student errors in solving story problems and to find out the relationship between self-efficacy and student errors in solving math story problems. This research uses mixed methods with quantitative and qualitative approaches. The research population was 330 students with a research sample of 32 students. The sampling technique used purposive random sampling and the determination of the number of samples using the Sloven formula. Collecting data using a questionnaire instrument, test questions, and interview guidelines. Data analysis techniques in the form of correlation test and descriptive statistics. The results showed the value of atau , dimana hasil tersebut lebih dari atau . This means that between self-efficacy and student errors in solving mathematical story problems with linear equations one variable has a negative relationship, namely the higher the student's self-efficacy, the lower the errors made by students. On the other hand, the lower the student's self-efficacy level, the higher the errors made by students in solving the story problems of the one-variable linear equation material